2015
DOI: 10.2174/1874944501508010010
|View full text |Cite
|
Sign up to set email alerts
|

Weight Status Among Somali Immigrants in Sweden in Relation to Sociodemographic Characteristics, Dietary Habits and Physical Activity

Abstract: Abstract:Background: Immigrants are considered globally to be a vulnerable subpopulation. Vulnerable population groups have a higher prevalence of obesity than the general population. Despite increased immigration of people from Somalia to Sweden in recent years, little research has been undertaken about obesity and obesity-related health risks among Somali immigrants. The present study aimed to investigate the prevalence of overweight and obesity, as well as possible relationships between weight status and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
4
3
0
Order By: Relevance
“…In the FINDRISC validation study by Lindström and Tuomilehto, the consumption of fruits and vegetables contributed little to the prediction of diabetes risk, but they still included it into the model to emphasize the importance of diet in T2D prevention [ 34 ]. The finding that the risk for diabetes was not associated with diet, which is found by our study, is consistent with a recent study in Sweden that found that sociodemographic factors are more important in a higher BMI among Somali women than diet [ 45 ]. Nonetheless, 50% of the participants in this study had a lower intake of fruits and vegetables.…”
Section: Discussionsupporting
confidence: 93%
“…In the FINDRISC validation study by Lindström and Tuomilehto, the consumption of fruits and vegetables contributed little to the prediction of diabetes risk, but they still included it into the model to emphasize the importance of diet in T2D prevention [ 34 ]. The finding that the risk for diabetes was not associated with diet, which is found by our study, is consistent with a recent study in Sweden that found that sociodemographic factors are more important in a higher BMI among Somali women than diet [ 45 ]. Nonetheless, 50% of the participants in this study had a lower intake of fruits and vegetables.…”
Section: Discussionsupporting
confidence: 93%
“…Also, younger refugees were exposed to many challenges to get jobs and looking for long-term goals which made them more responsible. Similar results were reported in the literature among refugees in Matlin, Depoux, Schütte, Flahault, and Saso (2018) and Torp et al (2015).…”
Section: Results Of Stress Management Domain Indicated That Syrian Ref-supporting
confidence: 92%
“…Similar results were reported in the literature among refugees in Matlin, Depoux, Schütte, Flahault, and Saso (2018) and Torp et al. (2015).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, they are a relatively new immigrant group, and the knowledge about their health status in both the host country and their country of origin is limited. Results from a few studies have shown that many Somali immigrants are overweight and obese due to nutritional transition, lack of physical activity, and other factors [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%